Screening of Wheat Genotypes with Heat Susceptibility Indices for Yield and it Attributing Characters under Different Sowing Conditions - Kumar, V. Umesh; Hazra, Soham; Gorai, Shouvik; Maji, Anirban; Ali, Nasim; Pal, Anjan Kumar (International Journal of Bio-resource and Stress Management, 2025)
An experiment was conducted during rabi (November–April of 2017–2018, 2018–2019) at AB-Block Farm, Kalyani, Bidhan Chandra Krishi Viswavidyalaya (B.C.K.V.), Nadia, and West Bengal, India to study the heat stress on wheat genotypes by identifying parents and its promising crosses on the basis of mean performance and heat susceptibility index. In the experiment, Heat susceptible indices (HSI) was used as criteria for evaluation and selection of genotypes under heat stress conditions and studied yield attributing characters of late sown (E2) in comparison of timely sown environment (E1) and very late sown (E3) in comparison of timely sown environment (E1). Screening of thirty genotypes were done in three different dates of sowing, among thirty genotypes four genotypes namely HTSBWYT-17-004, HTSBWYT-17-0020, HTSBWYT-17-0027 and HTSBWYT-17-0049 were identified as potential on the basis of maximum number of traits like pollen fertility, number of grains spike-1, yield plant-1, number of tillers plant-1, number tillers square meter-1 and 1000 grain weight that associated with HSI less than one (<1). These four selected parents and two checks DBW-39, K-1006 were crossed in 6×6 half diallel fashion. All parents and F1 were evaluated in three different dates of sowing, among Fifteen F1, four stable F1 for thermal stress across the three environments were HTSBWYT-17-004×HTSBWYT-17-0020, HTSBWYT-17-0020×K-1006, HTSBWYT-17-0020×HT49 and HTSBWYT-17-0027×HTSBWYT-17-0049 as these cross combinations recorded maximum number of traits associated with HSI less than one (<1).